SCREENING OF DEVELOPMENTAL DISORDERS IN CHILDREN BY USING THE STANDARDIZED QUESTIONNAIRES "AGES & STAGES QUESTIONNAIRES" (ASQ-3) - Makevic Djuric, Mirjana; Djuric, Milivoje (HEALTH CARE, 2023)
Introduction/Aim: By introducing a questionnaire for screening developmental disabilities in early childhood, developmental delay would be detected in time thus enabling prompt intervention. The standardized questionnaire "Ages and Stages Questionnaire" (ASQ-3) has been used for more than 30 years all over the world, and in Serbia it was standardized under the name "Uzrasti i razvoj deteta" (URD). The aim of our study was to identify children with developmental disabilities in early childhood using the standardized ASQ-3 questionnaire in primary pediatric practice, so that the appropriate treatment would be started on time.Methods: This study included 31 subjects aged 9-36 months. The subjects were divided into age groups and the standardized ASQ-3 questionnaire was used for each child. The obtained data were analyzed with the help of a computer program for statistical analysis of data (SPSS, version 20), and the methods of descriptive statistics were used.Results: The obtained results showed that 71% of the subjects suffered from developmental disorders, which demanded additional learning activities or further diagnostics. In 45.2% of the subjects, deviations from normal development were discovered in at least one of the examined areas, which demanded additional learning activities and further monitoring of children (that is, they had results in the grey zone), and in 25.8% of the subjects, deviations demanded consultations with experts for further assessment and treatment (that is, they had results in the black zone).Conclusion: The introduction of standardized ASQ-3 questionnaires as a mandatory clinical instrument in primary pediatric practice would enable early recognition of children with deviations from normative development, when early stimulation of development would begin, and the need for re-evaluation, supplementary diagnostics and early intervention support would be established.
Keywords: developmental disorders, early identification, early intervention, ASQ-3 questionnaire